Analisis SEM tentang Pengaruh Pendidikan dan Dukungan Keluarga terhadap Niat Wirausaha Melalui Sikap Wirausaha - Muhammad Akbar; Nurhasan Syah; Chairul Nazalul Anshar; Ganefri Ganefri; Asmar Yulastri; Yudha Aditya Fiandra (PAKAR Pendidikan, 2026)
The problem of this study lies in the suboptimal relationship between entrepreneurship education and students' entrepreneurial intention. Although students have acquired entrepreneurship learning, an increase in entrepreneurial intention does not always occur directly. This indicates a gap between the transfer of entrepreneurship knowledge and the formation of psychological dispositions, particularly entrepreneurial attitudes, as an important factor in shaping entrepreneurial intention. In addition, family support is often considered to play a role in encouraging entrepreneurial career choices, but empirical findings are inconsistent. This study focuses on analyzing the impact of entrepreneurship education and family support on entrepreneurial intention. using entrepreneurial attitude as a mediating variable in a structural equation model (SEM). The study used a quantitative approach, with a survey administered to 114 Building Engineering Education students from the 2022–2024 cohort who had taken entrepreneurship courses. Data collection was conducted using a Likert scale questionnaire (1–5) and analyzed using SEM to test direct and indirect effects among latent variables. The results showed that entrepreneurship education had a positive and significant effect on entrepreneurial attitudes and intentions. However, the direct effect of entrepreneurship education on intentions was not significant when attitudes were not included as a mediator. Meanwhile, family support did not have a significant effect on entrepreneurial attitudes. These findings confirm that entrepreneurial attitudes play an important role as a mediator in shaping students' entrepreneurial intentions.